Freedom of movement of capital and its impact on the effectiveness of monetary policy In Iraq (2005-2016) - سعيد عفراء هادي; محمد نور صباح (Journal of Economics and Administrative Sciences, 2019)
The interest in the issue of capital movement as an economic phenomenon has increased because of its effects and effects and its ability to influence the economic balance and the effectiveness of monetary policy. All countries seek to attract capital and benefit from it because of its effects and results such as supporting economic development process and optimal allocation of economic resources. The problem of the financing gap that most countries suffer from, and others, but sometimes the movement of capital creates challenges for monetary policy makers in achieving their goals. After 2003, the Iraqi economy witnessed an openness and economic liberalization unlike previous years, which witnessed isolation from the outside world because of the economic blockade imposed. The research focused on the impact of the movement of capital represented by the capital accounts and the financial account on the variables of monetary policy (exchange rate, , The interest rate) for the period (2016-2005). As a result of the financial liberalization witnessed by Iraq, capital inflows were influenced by monetary factors and other factors (such as security and political conditions). Therefore, the financial account deficit for most of the study years, 2014) affected by The lack of a relationship between the capital account, the financial account and the parallel exchange rate, the absence of a relationship between the capital account, the financial account and the interest rate, and the absence of a relationship between the financial account and the money supply.